2011
DOI: 10.1039/c0cp02198a
|View full text |Cite
|
Sign up to set email alerts
|

Unusual decrease in conductivity upon hydration in acceptor doped, microcrystalline ceria

Abstract: The impact of hydration on the transport properties of microcrystalline Sm 0.15 Ce 0.85 O 1.925 has been examined. Dense, polycrystalline samples were obtained by conventional ceramic processing and the grain boundary regions were found, by high resolution transmission electron microscopy, to be free of impurity phases. Impedance spectroscopy measurements were performed over the temperature range 250 to 650 1C under dry, H 2 O-saturated, and D 2 O-saturated synthetic air; and over the temperature range 575 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 40 publications
5
25
0
Order By: Relevance
“…[58][59][60][61] In fluorite-type oxides (Zirconia, Ceria), hydration appears to be more of a surface-interface process inside grain boundaries. 62,63 Kim et al did not observe any significant effect on the conductivity of nano-crystalline ceria in hydration experiments. 64 Recently, Gregori et al investigated the conductivity of dense and porous nanocrystalline ceria thin films at temperatures below 500 1C under wet and dry conditions.…”
Section: Conductivity and Defect-chemistry Of O-mayenite Depending Onmentioning
confidence: 94%
“…[58][59][60][61] In fluorite-type oxides (Zirconia, Ceria), hydration appears to be more of a surface-interface process inside grain boundaries. 62,63 Kim et al did not observe any significant effect on the conductivity of nano-crystalline ceria in hydration experiments. 64 Recently, Gregori et al investigated the conductivity of dense and porous nanocrystalline ceria thin films at temperatures below 500 1C under wet and dry conditions.…”
Section: Conductivity and Defect-chemistry Of O-mayenite Depending Onmentioning
confidence: 94%
“…3), the bulk conductivity is independent of grain size, over the entire temperature range. Furthermore, both the absolute magnitudes and the activation energies for charge transport associated with this arc, the latter set obtained from a fit of the temperature dependent behavior to the Arrhenius relation σT = σ 0 exp(−E/kT ) [ 8 ] are identical, within experimental error, to those of the bulk values of the microcrystalline material, 12 indicating that the slight variation in dielectric behavior and slight elevation in ε r relative to the microcrystalline value of 59 does not play a significant role in the transport properties.…”
Section: Ionic Conductivity Of Sdc At Ambient Po 2 -At Moderate Tempmentioning
confidence: 99%
“…The latter value is, in turn, another factor of ∼2 larger than the grain boundary thickness of the microcrystalline material, ∼1.2 nm. 12 With the above interpretation, C gi /C gb is taken to yield a meaningful microstructural parameter from which the specific grain boundary conductivities of the four samples can be computed according to σ spec gb = σ tot gb C gi /C gb . For the data obtained at 300…”
Section: Ionic Conductivity Of Sdc At Ambient Po 2 -At Moderate Tempmentioning
confidence: 99%
“…1 In recent years it has been observed that, upon nanostructuring, ceria can display significant proton conductivity at much lower temperatures than that required to activate oxide ion motion. The connection between grain size and magnitude of the proton conductivity in the nanostructured materials displaying this unusual phenomenon, as well as the observation that proton uptake and transport in bulk, microcrystalline ceria are negligible, [2][3][4] has led to the general consensus that the proton conduction occurs through a grain boundary (or surface) mediated process. 5,6 This insight suggests that a material with an aligned microstructure, with grain boundaries and/or open pore channels parallel to the path of proton transport, may lead to proton conductivities that are even larger than those reported to date.…”
Section: Introductionmentioning
confidence: 99%